2020
DOI: 10.1016/j.jtcme.2019.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical, hematological and histopathological evaluation of the toxicity potential of the leaf extract of Stachytarpheta cayennensis in rats

Abstract: Background and Aim The many pharmacological potentials of Stachytarpheta cayennensis (L.C. Rich) Vahl, especially in managing central nervous system disorders, hypertension, diabetes and infections, have made it a subject of abuse, necessitating the need to ascertain its safety. This study therefore investigated the toxic effects of the leaf extract of S. cayennensis in rats following acute and 28-day repeated doses in male and female rats. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 43 publications
7
43
0
Order By: Relevance
“…Experimental evidences have shown that exposure to certain plants, drugs, and compounds significantly alter haematological parameters. Thus, it is an important index of toxicity with high predictive potential for human toxicity [ 35 ]. The result of this study indicated that there was no significant (p > 0.05) alteration in most of the haematological indices (WBC, LYMPH, MID, GRAN, MCV, MCH, RDW, PLT, MPV, PDW, and PCT) studied except for erythrocytic indices, HGB, RBC, and HCT which showed a marginal but significant (p < 0.05) decline in the group treated with the highest dose of 600 mg/kgbw ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental evidences have shown that exposure to certain plants, drugs, and compounds significantly alter haematological parameters. Thus, it is an important index of toxicity with high predictive potential for human toxicity [ 35 ]. The result of this study indicated that there was no significant (p > 0.05) alteration in most of the haematological indices (WBC, LYMPH, MID, GRAN, MCV, MCH, RDW, PLT, MPV, PDW, and PCT) studied except for erythrocytic indices, HGB, RBC, and HCT which showed a marginal but significant (p < 0.05) decline in the group treated with the highest dose of 600 mg/kgbw ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Single-dose toxicity profiling was carried out in line with OECD guidelines 423 [ 19 ] as earlier reported [ 18 , 20 ]. In this study, four groups of rats containing randomly selected 6 rats per group were orally administered 250, 500, 1000 mg/kg body weight of emulsified EODS and 5% v/v Tween 80 (control) after an overnight fast.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, four groups of rats containing randomly selected 6 rats per group were orally administered 250, 500, 1000 mg/kg body weight of emulsified EODS and 5% v/v Tween 80 (control) after an overnight fast. Monitoring of weights and FOB by cage side observation were as previously described [ 18 , 20 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver and kidney are the primary organs responsible for the regulation of metabolic pathways, maintenance of body equilibrium and detoxi cation (Awasthi et al, 2018;Kumar et al, 2019;Ratn et al, 2018) therefore, mercury can affect these organs severely and impair their functional role by interfering with key physiological and metabolic processes. Assessment of different biomarkers in blood is an imperative and sensitive index, they play a crucial role in toxicological studies, the obtained experimental data help in clinical correlation (Olayode et al, 2020;Perveen et al, 2019).…”
mentioning
confidence: 99%